Entre polêmicas abertas e veladas - Brait, Beth; Pistori, Maria Helena Cruz; Lopes-Dugnani, Bruna; Melo Júnior, Orison Marden Bandeira de (Bakhtiniana. Revista de Estudos do Discurso, 2019)
Editorial 15.1